Analysis of That Influence Employee Performance: Work Environment, Leadership, and Mental Health: Literature Review from Human Resource Management Perspectives - Palinggi, Sarah Yarden; Agustina, Tri Siwi (Manunggal Halim Jaya, 2025)
Human resources are essential in a corporation because they reinforce other operational resources. This role can determine the progress or decline of a corporation. This research analyzes the influence of work environment, leadership, and mental health on employee performance. Using quantitative explanatory methodology, the study utilized Structural Equation Modeling with Partial Least Squares (SEM-PLS), which was used in this work via SmartPLS software. A structured survey was used to gather information from 105 workers. The findings reveal a positive relationship between work environment, leadership, and mental health on employee performance.